Monte carlo simulation by code of MCNP and experimental check for measuring thickness of materials for the spec raltzrng system of MYO-101 - Bui, Van Loat (H. : ĐHQGHN, 2017)
At present, thickness measurement of materials based on effect of backscattering gamma-ray has been widely used in industry in our country. The report presented research in measuring thickness of some materials such as paper, plastic, aluminum and steel with using the dedicated system of MYO-101, having scintillation detector of YAP(Ce) and gamma-ray of 60 keV of Am-241 source, by Monte-Carlo simulation using the code of MCNP. The simulation was checked by experimental measurements. The results were shown that they were in accordance with the range of error. This research has been useful for training activities with a view of human resowces development in the field of application of nuclear techni.que in industry in Vietnam.